2019
DOI: 10.14710/jksa.22.6.235-241
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity and Mechanism of Action of Methanol Extract from Kasturi Mango Fruit (Mangifera casturi) on Caries-Causing Bacterium Streptococcus mutans

Abstract: One of the problems frequently found in the oral cavity is dental caries caused by Streptococcus mutans. Thus far, dental caries is treated using antibiotics. However, the bacterium is known to be resistant to many antibiotics; hence, another alternative is needed. An alternative option is found in the Kasturi mango (Mangifera casturi). This study aims to identify the bioactive compounds of  Kasturi mango and find out the mechanism of its action in inhibiting the growth of Streptococcus mutans. Kasturi mangoes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…A study conducted by Rosyidah et al (2010) revealed that M. casturi's bark possesses antibacterial activity against E. coli and S. aureus. Extract and fraction of M. casturi fruit also reported possess antibacterial compound against Pseudomonas aeruginosa, Bacillus cereus (Meliana et al 2021) and Streptococcus mutant (Suhendar et al 2019) as well. Moreover, another part of M. casturi such as leaf extract either known to have antibacterial activity against S. mutant ( Khairiyah et al 2019) and Streptococcus san guinis (Sari et al 2020).…”
Section: Introductionmentioning
confidence: 92%
“…A study conducted by Rosyidah et al (2010) revealed that M. casturi's bark possesses antibacterial activity against E. coli and S. aureus. Extract and fraction of M. casturi fruit also reported possess antibacterial compound against Pseudomonas aeruginosa, Bacillus cereus (Meliana et al 2021) and Streptococcus mutant (Suhendar et al 2019) as well. Moreover, another part of M. casturi such as leaf extract either known to have antibacterial activity against S. mutant ( Khairiyah et al 2019) and Streptococcus san guinis (Sari et al 2020).…”
Section: Introductionmentioning
confidence: 92%
“…[43,45] Alkaloid ditemukan pada konsentrasi minimum di hampir semua tanaman. [40,41,42] Penghambatan adipogenesis sebenarnya masih perlu diteliti lebih spesifik mengenai kedua senyawa ini. [24]…”
Section: Pendahuluanunclassified
“…Measurement at 260 nm wavelength was conducted to observe the release of nucleic acids, while the 280 nm wavelength setting was applied to observe protein that emerged from the cells of test bacteria. An increase in the absorbance value after treatment indicated the test bacteria to have undergone lysis and leakage, hence making genetic materials, which took the form of nucleic acids and proteins, scattered and leave the cells (Suhendar et al, 2019).…”
Section: Analysis Of Protein and Nucleid Acid Leaksmentioning
confidence: 99%